Glissades Are Altered by Lesions to the Oculomotor Vermis but Not by Saccadic Adaptation - Flierman, Nico A.; Ignashchenkova, Alla; Negrello, Mario; Thier, Peter; De Zeeuw, Chris I.; Badura, Aleksandra (Frontiers in Behavioral Neuroscience, 2019)
Saccadic eye movements enable fast and precise scanning of the visual field. Therefore, accuracy and speed are crucial for processing visual information and are partially controlled by the posterior cerebellar vermis. Textbook saccades have a straight trajectory and a unimodal velocity profile, and hence have well-defined epochs of start and end. However, in practice only a fraction of saccades matches this description. One way in which a saccade can deviate from its trajectory is the presence of a saccadic overshoot or undershoot at the end of a saccadic eye movement just before fixation. This additional movement, known as a glissade, is regarded as a motor command error and was characterized decades ago but was almost never studied. Using rhesus macaques, we investigated the properties of glissades and changes to glissade kinematics following cerebellar lesions. Additionally, in monkeys with an intact cerebellum, we investigated whether the glissade amplitude can be modulated using multiple adaptation paradigms. Our results show that saccade kinematics are altered by the presence of a glissade, and that glissades do not appear to have any adaptive function as they do not bring the eye closer to the target. Quantification of these results establishes a detailed description of glissades. Further, we show that lesions to the posterior cerebellum have a deleterious effect on both saccade and glissade properties, which recovers over time. Finally, the saccadic adaptation experiments reveal that glissades cannot be modulated by this training paradigm. Together our work offers a functional study of glissades and provides new insight into the cerebellar involvement in this type of motor error.